Examining volatility spillover between Asian countries' stock markets - Khalil Jebran; Amjad Iqbal (China Finance and Economic Review, 2016)
Background: This study examined the volatility spillover effects between the stock markets of Asian countries, i.e., Pakistan, India, Sri Lanka, China, Japan, and Hong Kong. Methods: The daily data was considered from the period 4 January 1999 to 1 January 2014, consisting five trading days from Monday to Friday. The volatility spillover between stock markets was captured by using the generalized autoregressive conditional heteroskedasticity (GARCH) model. Results: The empirical analyses show evidence of significant bidirectional spillover of return and volatility between China and Japan. The results also show significant bidirectional volatility transmission between the equity markets of the following countries: Hong Kong and Sri Lanka, China and Sri Lanka. The significant unidirectional transmissions of stock market volatility are found to be flowing from India to China, Sri Lanka to Japan, Pakistan to Sri Lanka, and Hong Kong to India and Japan. Conclusions: These results are important for economic policy makers in order to safeguard the financial sector from international financial shocks. The investors can use this information for making efficient portfolio which will reduce their risk and enhance their returns.
Keywords: 330; Volatility spillover; Asian countries; GARCH model; Time series analyses